Knowledge Conversion by Freelancers in the Field of Cultural and Creative Industries - Alberto Gonzalez-Cristiano (United Kingdom, 2022)
The importance of knowledge as a company’s resource has been a topic that has interested researchers for already a number of years (e.g. Mahr, Lievens and Blazevic 2013; Nonaka and Takeuchi 1995; Teece, Pisano and Shuen 1997). As companies realize the relevancy of knowledge as their main source of competitive advantage (Nonaka 1991, 96; Vargo and Lusch 2004, 9) and as we move towards a knowledge-based economy (e.g. Drucker 1990; Foray 2004), we see a shift towards knowledge-intensive activities (Foray 2004, 18). In this context, codification of knowledge becomes an essential part of economic action (Steinmueller 2000, 362) and codified knowledge is seen as a key characteristic of the development of modern economies (Ancori, Bureth and Cohendet 2000, 256). In this modern economies, we find evidence of the importance of the knowledge-intensive field of cultural and creative industries (CCIs), both in public administration (e.g. EC 2010) and in academic research (e.g. Potts and Cunningham 2008). Moreover, although industries operating in this sector have higher human capital than the aggregate economy (Potts and Cunningham 2008, 176), this field is mainly formed by freelancers (Europa Innova 2011, 9) who have been systematically neglected by academic literature (Leighton 2015). Due to the importance of knowledge, there is a need to focus on the routines and processes organizations use to acquire, assimilate, transform, and exploit it (Zahra and George 2002, 199), but also to keep in mind that the practices followed by freelancers are likely to differ because of their need to compensate their lack of internal processes by relaying on external ones (Lichtenthaler 2011, 82). Taking this context into account, this article has the objective to look at knowledge conversion in development processes by freelancers in the field of CCIs. The aim of this article is twofold. Firstly, it aims at providing a plausible explanation on how knowledge conversion occurs between clients and freelancers in development processes. Secondly, due to the special characteristics of CCIs (Potts et al, 2008, 168) and the heterogeneity of freelancers (Rapelli 2012, 7), this article aims at analysing how this knowledge conversion process has differences or similarities with models applicable to larger organizations and/or different fields. In order to address these two aims, this paper relies on a dataset comprising twelve development projects. More specifically, primary data were collected in Spain through semi-structured interviews conducted with seven freelancers in January and February 2016. Alongside, secondary data were used with the aim of triangulation. The analysis of these data exposed a general knowledge transfer process in which freelancers engage with the aim of understanding and codifying client’s knowledge. The process starts with the creation of an abstract, general, concept which is then turned into stories, keywords and more concrete concepts that are used as the raw material for the final design. The analysis of the interviews revealed certain patterns related to knowledge conversion with a focus on dialogue between client and designer, and the use of metaphors and boundary objects as means to assure the achievement of shared understanding.
Proceedings of the 17th European Conference on Knowledge Management